Can religious belief be explained away? Reasons and causes of religious belief - Barrett, J; Leech, D; Visala, A (Tectum Verlag, 2010)
The Nature of God - Evolution and Religion: To explain religious behavior is a daunting task. One very recent attempt is to explain religious behaviors and religion within an evolutionary framework. In this volume leading experts from various disciplines analyze religion and religiosity as phenomena in a Darwinian world. Is religiosity adaptive? Are religious people more fertile? Do we have cognitive predispositions to be religious? Are children natural believers? These questions are answered in this fascinating array of contributions from the field of evolutionary studies of religion.